Decline in beetle abundance and diversity in an intact temperate forest linked to climate warming. (December 2019) - Harris, Jennifer E.; Rodenhouse, Nicholas L.; Holmes, Richard T.
Abstract: Insect abundances are declining in many areas around the world, but the causes of those declines are seldom clear. Here we report a dramatic decline in the abundance and diversity of Coleoptera (beetle) taxa in a large tract of intact northern hardwood forest during the last 45 years, and provide evidence supporting winter warming as the primary cause. Beetles were sampled using the same method (window traps) and in the same locations within the Hubbard Brook Experimental Forest, New Hampshire, in 1973–1977 and again in 2015–2017. The mean (±SE) number of beetles captured per 48-h fell from 23.2 (±3.89) to 3.9 (±1.19), a decline of 83% over this 45-year period. The number of beetle taxa captured decreased by 39%, with 19 beetle families disappearing entirely. Beetle capture rate was least when and where climate was warmest. Capture rate was significantly lower in the 2010s when mean daily temperature was about 1.8 °C warmer, and sampling during 2016–2017 at low, mid and high elevations (320, 540, and 810 m asl, respectively) revealed lowest beetle captures at low elevation where climate was warmest. Most importantly, beetle capture rate was significantly lower after winters with less snow cover during the previous winter, indicating that snow cover in northern hardwood forest is essential for sustaining the beetle community. These results imply that additional climate warming might further reduce the abundance and diversity of beetles and other arthropods inhabiting the forest-floor, potentially affecting critical ecosystem processes such as decomposition and carbon storage. Highlights: Coleoptera abundance and diversity dropped steeply between mid 1970s and mid 2010s. Beetle abundance, all taxa combined, declined by 83% between the sampling periods. The number of taxa detected was 39% less in 2015–2017 compared to mid 1970s. Predaceous beetles declined the most. Reduced snow depth and duration were identified as the major causes of the declines.